THE EFFECTIVENESS OF PRIMARY HEALTH CARE REFORMS IN UZBEKISTAN TOWARDS ACHIEVING UNIVERSAL HEALTH COVERAGE: A COMPREHENSIVE ANALYSIS - Saidov Suhrob Shodmonovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT. Between 2010 and 2018, Uzbekistan implemented an Economic Adjustment Program and a series of broad reforms, including in the health sector. We conducted a large-scale review to examine whether reforms in the primary health care system during that period helped the country transition to universal health coverage.